Biggs on finance, economics, and the stock market : Barton's market chronicles from the Morgan Stanley years - Biggs, Barton, 1932-2012 (Hoboken, New Jersey : Wiley, 2014)
Long considered one of the best brains on Wall Street, Barton Biggs acquired the stature of a legend within his lifetime. Among his many coups, he accurately called the rise and fall of the dot-com market, and was an energetic promoter of emerging markets, including China, well before American businesses began flocking there - and he made vast fortunes for his clients, in the process.
Includes bibliographical references.
Keywords: Biggs, Barton, -- 1932-2012 -- Correspondence; Investment advisors -- United States -- Correspondence; Finance -- United States; Investments -- United States